Improving the Reading Comprehension of Eleventh Grade Students at SMK Madyatama Palembang through the Use of the Keyword Method: A Classroom Action Research: English - Fadhilah Khairani; Tahrun; Mulyadi (Journal of English Development, 2024)
This study was to find out how much students' reading comprehension improved after the application of Keyword Method, as well as how involved the eleventh grade students at SMK Madyatama Palembang were in the learning process. Three cycles of classroom action research, or CAR, are used in the research procedure. This study is focused on improving the real condition of the English teaching and learning process to teach the improvement of the students’ reading comprehension. The findings showed that there is a significant improvement of students’ reading comprehension by using the application of keyword method. The students’ improvement in reading skill as shown in cycle 1 was 23%, cycle 2 was 65%, and cycle 3 was 88%. It is concluded that the use of Keyword Method effectively improves the Eleventh Grade Student’s Reading Comprehension at SMK Madyatama Palembang.